Moving Towards a Single Labor Contract: Transition vs. Steady State - Nawid Siassi; Juan J. Dolado; Etienne Lalé (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper analyzes the optimal design of a single open-ended contract (SOEC) and studies the political economy of moving towards such a SOEC in a dual labour market. We compare two economic environments: one with flexible entry-level jobs and high employment protection at long tenure, and another with a SOEC featuring employment protection levels that increase smoothly with tenure. For illustrative purposes, we specialize the discussion of such choices to Spain. A SOEC has the potential of bringing big time efficiency and welfare gains in a steady-state sense. We also identify winners and losers in the transitional path of such a reform and analyze its political support.
Keywords: H29; J33; J65; 330